Incidental detection of thyroid metastases from renal cell carcinoma using 68Ga-PSMA PET/CT to assess prostate cancer recurrence - Zacho, Helle Damgaard; Haberkorn, Uwe (Clinical nuclear medicine, 2017)
68Ga-PSMA PET/CT is increasingly used to assess prostate cancer. Avid 68Ga-PSMA uptake by thyroid cancer and renal cell carcinoma (RCC) has been reported in few cases. A 75-year-old man who received a diagnosis of RCC in 2006 and prostate cancer in 2009 presented with elevated prostate-specific antigen levels (0.7 ng/mL) following prostatectomy. 68Ga-PSMA PET/CT showed avid 68Ga-PSMA uptake in 1 pelvic and 1 retroperitoneal lymph node and focal 68Ga-PSMA accumulation in the thyroid. Excised retroperitoneal lymph node and thyroid tissues showed metastases from RCC, whereas the pelvic lymph node exhibited metastasis from prostate cancer.